Editorial - The Australian Journal of Indigenous Education (The Australian Journal of Indigenous Education, 2012)
What is the state of play in Indigenous education today? What kind of thinking is driving the reform agenda in Indigenous education right now? What kinds of gains have we made and what work is there yet to do? In an era of unprecedented ‘gap’ talk, these are pressing questions, which the articles in this issue address and explore.